2013
DOI: 10.1097/dcr.0b013e31827f0697
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Sacral Nerve Stimulation for Fecal Incontinence in Patients Refractory to Percutaneous Tibial Nerve Stimulation

Abstract: Sacral nerve stimulation appears to be an effective treatment for patients who do not gain an adequate therapeutic benefit from percutaneous tibial nerve stimulation and, thus, should be routinely considered for this patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Within-group effect estimates were in general larger for SNS, based on analysis of all patients embarking on treatment, with greater benefits still in patients who progressed to permanent implantation. This finding is in keeping with non-randomized comparisons of SNS and PTNS 36 . Although the present data are insufficient to advise on whether PTNS should be offered as an alternative to SNS, based on efficacy, the study does indicate that both treatments are highly acceptable to patients, with some expressing a preference for one treatment over the other.…”
Section: Discussionsupporting
confidence: 88%
“…Within-group effect estimates were in general larger for SNS, based on analysis of all patients embarking on treatment, with greater benefits still in patients who progressed to permanent implantation. This finding is in keeping with non-randomized comparisons of SNS and PTNS 36 . Although the present data are insufficient to advise on whether PTNS should be offered as an alternative to SNS, based on efficacy, the study does indicate that both treatments are highly acceptable to patients, with some expressing a preference for one treatment over the other.…”
Section: Discussionsupporting
confidence: 88%
“…7,8 The short-and mid-term success of SNM in patients with FI has been demonstrated in several studies. [9][10][11] Recently, studies with long-term follow-up have shown a lasting effect. [12][13][14] Data regarding constipation are rare, particularly data with a long-term followup.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the posterior tibial nerve is being increasingly utilized as a nerve stimulation site because of the added advantage of percutaneous and transcutaneous therapy, rather than invasive lead placement. Hotouras et al [31] observed that 68.4% of their patients who did not have improvement in symptoms with PTNS (n ¼ 20) reported a decrease in incontinence after SNS. To elucidate the optimal route for PTNS, George et al [30 && ] conducted a randomized controlled trial comparing percutaneous PTNS (n ¼ 11), transcutaneous PTNS (n ¼ 11), and sham transcutaneous PTNS (n ¼ 8).…”
Section: Nerve Stimulation Techniquesmentioning
confidence: 96%